2023
DOI: 10.1007/s11104-023-05908-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant-soil feedback: incorporating untested influential drivers and reconciling terminology

Abstract: Background Plants condition the soil in which they grow, thereby altering the performance of subsequent plants growing in this soil. This phenomenon, known as plant-soil feedback (PSF), has garnered increasing interest. Experiments are moving from single species soil pairings in the glasshouse to community-level field trials. Consequently, our knowledge of the role PSF plays in shaping ecosystem functions has advanced. However, knowledge gaps remain. Scope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 360 publications
1
19
0
Order By: Relevance
“…Since their discovery, PSF have been formally presented in the context of effects and responses to the 'soil community' (Bever, 1994) and 'specific growth-depressing microorganisms' ( Van der Putten et al, 1993). This microbe-centric perspective is important, and still predominant, but the role of plant and soil chemistry is gaining attention (Mazzoleni et al, 2015;Nettan et al, 2019;Veen et al, 2019;Ehlers et al, 2020;De Long et al, 2023b;Nannipieri et al, 2023;Steinauer et al, 2023). For example, Semchenko et al (2019) experimentally manipulated soil chemical interactions and microbial legacies and found that belowground chemistry and soil biota interacted to promote seedling survival and species coexistence in grassland mesocosms.…”
Section: Integrating the Soil Metabolome Into Psf Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Since their discovery, PSF have been formally presented in the context of effects and responses to the 'soil community' (Bever, 1994) and 'specific growth-depressing microorganisms' ( Van der Putten et al, 1993). This microbe-centric perspective is important, and still predominant, but the role of plant and soil chemistry is gaining attention (Mazzoleni et al, 2015;Nettan et al, 2019;Veen et al, 2019;Ehlers et al, 2020;De Long et al, 2023b;Nannipieri et al, 2023;Steinauer et al, 2023). For example, Semchenko et al (2019) experimentally manipulated soil chemical interactions and microbial legacies and found that belowground chemistry and soil biota interacted to promote seedling survival and species coexistence in grassland mesocosms.…”
Section: Integrating the Soil Metabolome Into Psf Researchmentioning
confidence: 99%
“…Since their discovery, PSF have been formally presented in the context of effects and responses to the ‘soil community’ (Bever, 1994) and ‘specific growth‐depressing microorganisms’ (Van der Putten et al ., 1993). This microbe‐centric perspective is important, and still predominant, but the role of plant and soil chemistry is gaining attention (Mazzoleni et al ., 2015; Nettan et al ., 2019; Veen et al ., 2019; Ehlers et al ., 2020; Gundale & Kardol, 2021; De Long et al ., 2023b; Nannipieri et al ., 2023; Steinauer et al ., 2023). For example, Semchenko et al .…”
Section: Integrating the Soil Metabolome Into Psf Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant performances during the response phase are measured to predict how soil microbes influence plant coexistence (Crawford et al, 2019, Yan et al, 2022. However, despite a vast body of literature showing that soil microbes can exert strong controls over plant species coexistence, connecting the predictions from such two-phase studies to the observed dynamics of plant communities in nature remains challenging (Forero et al, 2019, Beals et al, 2020, Beckman et al, 2022, Png et al, 2023. A promising approach for addressing this challenge is to adopt the classic two-phase design to better reflect the natural conditions under which PSF arises in the field (Gundale & Kardol, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, microbial metabolism is the great engine of carbon and nutrient cycling contributing to the availability of soil nutrients (Willey et al, 2008). Overall, alterations of these mechanisms at the soil level may exert positive or negative effects on plant growth and fitness (Bezemer et al, 2020) and hence on species composition and ecosystem functioning (Png et al, 2023). Disentangling the individual contribution of the different processes involved in these plant-soil feedback and its responses to natural and anthropogenic disturbances associated with climate change (van der Putten et al, 2016) may further facilitate the implementation of effective climate-adaptive forest management (Refsland et al, 2023).…”
Section: Introductionmentioning
confidence: 99%